PERANCANGAN E-MARKETPLACE HASIL PERTANIAN DI WILAYAH KABUPATEN TOBA BERBASIS WEB - Alex Leo Nardo Sipayung; Marlyna Infryanty Hutapea; Jamaluddin Jamaluddin (Universitas Methodist Indonesia, 2022)
Toba Regency is one of the jurisdictions of North Sumatra Province which is located in a highland area with an altitude of 900-2200 meters. Most of the people in the Toba Regency area are farmers, ranchers and planters. At this time the development of information technology has grown very rapidly and affects all aspects of everyday life. So far, the sale of agricultural products in general is still using the traditional way where farmers still bring their agricultural products to the nearest market, making it difficult for farmers to sell agricultural products, and farmers can only rely on distributors and retailers to sell agricultural products, resulting in relatively low selling prices. cheap for farmers. E-marketplace is an electronic market that is used to carry out an activity or business activity between buyers and sellers to transact with each other. The purpose of this research is to facilitate the sale of agricultural products and make it easier for buyers to find the desired agricultural products. This website was developed using PHP and MySQL as the database. With the design of this e-marketplace, it can help local farmers in increasing the sales turnover of agricultural products because they can transact widely through the help of e-marketplaces. Keywords : System , Information System , E-marketplace, Database